Hybrid 7-Level Boost Active-Neutral-Point-Clamped (H-7L-BANPC) Inverter - Lee, Sze Sing; Lim, Chee Shen; Siwakoti, Yam P.; Lee, Kyo Beum (IEEE Transactions on Circuits and Systems II: Express Briefs, 2020)
The emerging active-neutral-point-clamped (ANPC) inverters with voltage-boosting capability are attractive for their low dc-link voltage requirement. These low voltage requirements enable a single-stage dc-Ac power conversion, which improves the overall efficiency, reliability, and power density of the system. A high voltage gain of 1.5 was demonstrated in recent boost type ANPC topology; however, it was achieved at the expense of high voltage stress on some of its switching devices. This brief proposes an improved topology with reduced voltage stress and a lower number of components while retaining the merits of high voltage gain. The proposed topology is a hybrid of a T-Type inverter and an H-bridge, which require only one floating capacitor and one less power switch than the aforementioned topology. One floating capacitor with self-voltage balancing capability is integrated to generate 7 output voltage levels. The proposed topology is analyzed and compared with recent boost ANPC topologies. Experimental results are presented for validation.
Keywords: Active neutral point clamped; DC-AC power conversion; Floating capacitor; High voltage gain; High-voltage stress; Number of components; Overall efficiency; Voltage balancing; 7-level; boost ANPC; multilevel inverter; voltage-boosting